2007
DOI: 10.4314/thrb.v9i2.14311
|View full text |Cite
|
Sign up to set email alerts
|

The vulnerability of orphans in Thyolo District, southern Malawi

Abstract: It is estimated that Malawi has about 900,000 orphans, the majority of whom are orphaned as a result of AIDS. Orphans in rural areas are mostly neglected by economic and social empowerment initiatives. This study was conducted to explore the living situation of orphans in rural Thyolo District, southern Malawi. Qualitative methodology was used in data collection and analysis to explore orphan children's living situation and specifically with regard to access to health care, education, food and basic needs. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 15 publications
2
24
0
1
Order By: Relevance
“…This finding is consistent with other investigations where children affected by AIDS were found to exhibit higher risk behaviours compared to other children [2,15,[46][47][48][49].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with other investigations where children affected by AIDS were found to exhibit higher risk behaviours compared to other children [2,15,[46][47][48][49].…”
Section: Discussionsupporting
confidence: 93%
“…Participants described being treated less well than other children, most often the caregivers’ biological children. This involved being deprived of resources such as food, clothing and schooling (Ansell & Young, 2004; Cluver & Gardner, 2007; Foster, Makufa, Drew, Mashumba, & Kambeu, 1997; Funkquist, Eriksson, & Muula, 2007; Harms, Jack, Ssebunnya, & Kizza, 2010; McGraw & Wameyo, 2005; Nyambedha, Wandibba, & Aagaard-Hansen, 2003; Nyamukapa et al, 2010; Oleke, Blystad, Fylkesnes, & Tumwine, 2007; Oleke, Blystad, Moland, Rekdal, & Heggenhougen, 2006; Snipstad, Lie, & Winje, 2005; van Blerk & Ansell, 2007; Young & Ansell, 2003) or being made to engage in excess chores or paid work (Ansell & Young, 2004; Harms et al, 2010; McGraw & Wameyo, 2005; Mojola 2011; Nyambedha et al, 2003; van Blerk & Ansell, 2007; Young & Ansell, 2003): “[My uncle] had many children, and he favoured them when we shared food and gifts, and I was overworked like a slave” (Ansell & Young, 2004). …”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (10/15) reported severe material deprivation such as hunger, tattered clothing and inadequate conditions: “At times I go to school, but not often because I don’t have clothes and food” (Funkquist et al, 2007). Several studies depicted experiences of overt neglect (Cluver & Gardner, 2007; McGraw & Wameyo, 2005; Nyamukapa et al, 2010; Oleke et al, 2006; Young & Ansell, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Third, we provide a contemporary appraisal by analyzing relatively recent data from the 2010 Nigeria Education Data Survey (NEDS). Fourth, we broaden the empirical focus beyond the typical restriction to primary-school-aged children aged 5-11 years 5 (Lloyd and Blanc 1996;Ainsworth and Filmer 2002;Yamano and Jayne 2005;Evans and Miguel 2007;Funkquist et al 2007;Parker and Short 2009) to children aged 4 to 16, and thus at both primary or secondary school levels. In so doing, we acknowledge both the value children and their guardians place on schooling beyond the primary school level (Yamano et al 2006) and the reality that the death of a parent can occur at any point during a child's schooling trajectory.…”
Section: Introductionmentioning
confidence: 99%